EFEKTIFITAS KOMUNIKASI DOKTER TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RSU IMELDA PEKERJA INDONESIA KOTA MEDAN - Erlina Rambe; Tri Niswati Utami; Jamaluddin - (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2021)
Communication between patient and doctor involves deep interaction between the two parties. This study aims to analyze the effectiveness of doctor communication on the satisfaction of outpatients at the General Hospital. Imelda Medan Indonesian Workers. This study is an analytic survey with a cross sectional study design conducted at the General Hospital. Imelda Medan Indonesian Workers Years from May to June 2020. The population in this study is the population in this study were all patients who visited as many as 76 people. Sampling was done in total sampling. Research data were analyzed using the Chi Square formula and logistic regression. Based on the results of the study note that there is an influence of openness (openess) of doctors on the satisfaction of outpatients in public hospitals. Imelda Medan Indonesian Workers, there was the influence of Emphaty (empathy) doctors on the satisfaction of outpatients in the General Hospital. Imelda Medan Indonesian Workers, there is an influence of the attitude (supportiveness) of doctors on the satisfaction of outpatients in the General Hospital. Imelda Medan Indonesian Workers, there is an effect of the equality of doctors on the satisfaction of outpatients in the General Hospital. Imelda Medan Indonesian Workers. This study suggests that doctors can continue to improve their communication skills or abilities so as to make patients open, have a supportive, positive attitude and equality so that doctors can get the information needed and provide appropriate treatment to patients and patients recover.